Meta‐analysis: Placebo rates in microscopic colitis randomised trials and applications for future drug development using a historical control arm. Issue 8 (24th February 2023) - Hamilton, Patrick; Buhler, Katherine; MacDonald, John K.; Kaplan, Gilaad G.; Seow, Cynthia H.; Lu, Cathy; Novak, Kerri L.; Andrews, Christopher N.; Singh, Siddharth; Jairath, Vipul; Panaccione, Remo; Ma, Christopher
Summary: Background: Effective medical therapies for patients with microscopic colitis (MC) who fail budesonide are lacking. However, conducting randomised controlled trials (RCTs) in MC has been challenging due to small sample sizes. Understanding placebo responses can help inform more efficient future trials. Aims: The aim of this study is to estimate clinical and histologic placebo response rates and to determine factors associated with placebo response in MC. Methods: EMBASE, MEDLINE, and CENTRAL were searched until 7 January 2022, to identify placebo‐controlled RCTs in adult patients with MC. Clinical and histologic response in the placebo arms were pooled using random‐effects models. Stratified analyses based on disease‐ and trial‐level characteristics, leave‐one‐out meta‐analysis, and cumulative meta‐analysis were performed. Results: Twelve RCTs enrolling a total of 391 patients (placebo n = 163) with MC were included. Pooled clinical and histologic placebo response rates were 24.4% (95% CI: 12.4%–38.4%), I 2 = 60.8%, p < 0.01, and 19.9% (95% CI: 5.3%–39.0%), I 2 = 66.4%, p = 0.01 (tests for heterogeneity), respectively. Clinical response to placebo was numerically higher in patients with lymphocytic compared to collagenous colitis (39.9% vs. 19.8%, p = 0.08). Heterogeneity in clinical response to placebo was significantly reduced when the Miehlke 2014 RCT was excluded in the leave‐one‐out meta‐analysis or when a more stringent secondary definition of response based on the Hjortswang criteria was applied. Conclusions: Approximately one‐quarter of patients in MC trials respond to placebo, although with substantial heterogeneity, reflecting the need for standardised outcome definitions and study designs for MC. This analysis also serves to inform future MC trials that may consider incorporating an external, historical placebo control arm, rather than directly randomising patients to placebo. Abstract : Response rates to placebo meta‐analyzed from all historical randomized controlled trials in microscopic colitis, demonstrating that approximately one quarter of patients will experience clinical response and 20% will achieve histologic response. Although there is significant heterogeneity in these estimates, much of the heterogeneity is driven by one trial and due to differences in primary outcome definitions, which requires standardization.